P128 A subgroup analysis of the efficacy of filgotinib for patients with moderately active RA following an inadequate response to methotrexate. (26th April 2021) - Buch, Maya H; Walker, David; Kiely, Patrick D W; Edwards, Christopher J; Barry, Jane; McCaughey, Gerard; Akroyd, Laura; Tiamiyu, Iyabode; Ye, Lei; Chen, Kun; Taylor, Peter C
Abstract: Background/Aims Filgotinib is an oral, preferential janus kinase 1 inhibitor. FINCH 1 (NCT02889796) was a phase III, double-blind, placebo- and active-controlled study evaluating filgotinib efficacy and safety in patients with rheumatoid arthritis (RA) after inadequate response to methotrexate (MTX; MTX-IR). Methods MTX-IR patients with moderately or severely active RA were randomised (3:3:2:3) to filgotinib 200 mg daily, filgotinib 100 mg daily, adalimumab 40 mg every 2 weeks, or placebo on a background of stable MTX for up to 52 weeks. An exploratory subgroup analysis of FINCH 1 was conducted in patients with moderately active RA based on Disease Activity Score in 28 joints with C-reactive protein (DAS28[CRP])>3.2-≤5.1 at baseline. Proportion of patients achieving 20%/50%/70% improvement from baseline in American College of Rheumatology core criteria (ACR20/50/70), DAS28(CRP)≤3.2, DAS28(CRP)<2.6, change from baseline in Health Assessment Questionnaire-Disability Index (HAQ-DI), Short Form-36 Physical Component Score (SF-36 PCS), patient-reported pain, and modified total Sharp/van der Heijde score (mTSS) were assessed at week (W)12 and W24. All analyses were exploratory without multiplicity adjustment; nominal P -values are reported. Results Of 1, 755 treated patients, 24% had moderate disease at baseline with similar proportions (21.9%-26.9%) across treatment groups. In each treatment arm, baseline characteristics were well balanced for the moderate disease activity subpopulation. The majority (77%) were female, mean (standard deviation [SD]) duration of RA was 7.8 (7.7) years; mean (SD) baseline DAS28(CRP) was 4.6 (0.42). At W12 and W24, proportions achieving ACR20/50/70, DAS28(CRP)<2.6, and DAS28(CRP)≤3.2 were significantly higher for both filgotinib doses relative to placebo (Table ). Improvement in HAQ-DI was significantly greater vs placebo at W12 but not W24 for both filgotinib doses (Table 1 ). For both doses of filgotinib vs placebo, SF-36 PCS and pain were significantly improved and there was numerically less radiographic progression as assessed by mTSS at W12 and W24 (Table ). Composite disease activity, HAQ-DI, and mTSS scores with both filgotinib doses were comparable to adalimumab. Conclusion In a subgroup of patients from FINCH 1 with baseline moderately active RA, significantly greater improvements in disease activity were observed with both filgotinib doses over placebo and associated with lower radiographic progression and reduced functional deficit. Disclosure M.H. Buch: Consultancies; MHB reports serving as a consultant for AbbVie; Eli Lilly; Gilead Sciences, Inc.; Sandoz; Sanofi; and Serono. Grants/research support; MHB reports grants or research support from Pfizer, Roche, and UCB. D. Walker: Grants/research support; DW has received funding from Bristol-Myers Squibb; Eli Lilly; Gilead Sciences, Inc.; Novartis; and Pfizer, Inc. P.D.W. Kiely: Other; PK has attended advisory boards, been part of a speakers bureau, or received support to attend educational meetings from AbbVie, Gilead, Lilly, Novartis, and Sanofi. C.J. Edwards: Consultancies; CJE has provided consultancy for AbbVie; Biogen; Bristol-Myers Squibb; Celgene; Eli Lilly; Fresenius; Gilead Sciences, Inc.; GSK; Janssen; MSD; Mundipharma; Pfizer; Roche; Samsung; and Sanofi. Member of speakers' bureau; CJE has served on speaker's bureaus for AbbVie; Biogen; Bristol-Myers Squibb; Celgene; Eli Lilly; Fresenius; Gilead Sciences, Inc.; GSK; Janssen; MSD; Mundipharma; Pfizer; Roche; Samsung; and Sanofi. Grants/research support; CJE reports grants from AbbVie; Biogen; Bristol-Myers Squibb; Celgene; Eli Lilly; Fresenius; Gilead Sciences, Inc.; GSK; Janssen; MSD; Mundipharma; Pfizer; Roche; Samsung; and Sanofi. J. Barry: Corporate appointments; JB is an employee of Gilead Sciences Ltd. G. McCaughey: Corporate appointments; GMcC is an employee of Gilead Sciences Ltd. L. Akroyd: Corporate appointments; LA is an employee of Gilead Sciences Ltd. I. Tiamiyu: Corporate appointments; IT is an employee of Gilead Sciences, Inc. L. Ye: Corporate appointments; LY is an employee of Gilead Sciences, Inc. K. Chen: Corporate appointments; KC is an employee of Gilead Sciences, Inc. P.C. Taylor: Consultancies; PCT has served as a consultant to AbbVie, Biogen, Galapagos, Gilead, GlaxoSmithKline, Janssen, Lilly, Pfizer, BMS, Roche, Sanofi, Nordic Pharma, Fresenius, and UCB. Grants/research support; PCT reports research grants from Gilead Sciences, Inc.; Galapagos, and Celgene.